Deep remission on magnetic resonance imaging impacts outcomes of perianal fistulizing Crohn's disease. Issue 3 (March 2019) - Chambaz, Marion; Verdalle-Cazes, Mikael; Desprez, Charlotte; Thomassin, Lucie; Charpentier, Cloé; Grigioni, Sébastien; Armengol-Debeir, Laura; Bridoux, Valérie; Savoye, Guillaume; Savoye-Collet, Céline
Abstract: Background: The long-term management of perianal Crohn's disease for patients on anti-TNF-α therapy remains challenging. Aim: To evaluate the long-term course and complications of patients with perianal fistulas treated with anti-TNF-α based on their clinical remission and healing on MRI. Methods: Patients were evaluated clinically and by MRI. Deep remission was defined as clinical remission associated with the absence of contrast enhancement and T2 hyperintensity on MRI. Flare-free survival, surgery and hospitalizations were compared based on the presence or not of deep remission. Results: Forty-eight consecutive patients were included with a median follow-up of 62 months after anti-TNF-α first administration. Deep remission was observed in 16 patients (33.4%). For patients in deep remission, the median time to any perianal event was 116 months (95–130) versus 42 months (8–72) in patients with pathological MRI (p < 0.001). Sixteen patients (50%) with pathological MRI had perianal surgery versus 2 (12.5%) in the deep remission group (p < 0.05). The mean duration of cumulative hospital stays was 0.75 ± 0.52 days in the deep remission group versus 19.7 ± 7.4 in the pathological group (p < 0.05). Conclusions: Higher flare-free survival and lower rates of surgery and hospitalization were found in patients achieving deep remission.